DASHBOARD PENGUKURAN KINERJA PROGRAM STUDI PERGURUAN TINGGI - Oktovianus Irvan; Jap Tji Beng; Dedi Trisnawarman (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
Dashboard is a tool that used for serving information in diagram model, visual indicator or graphic that make simply summary of information. Purpose of the thesis is to make an application for development dashboard that could used for measuring the performance of study program. Method that used is Extract, Transform, Load (ETL) and Method Software Engineering. ETL Method is importing the data to SQL SERVER and then transform it into a data master which easier to process to be a fact table data and ready to be the database master, and the software engineering method is a method Business Intelligence development derived from the method of software engineering is justification, planning, Business Analysis, Design, Construction, Deployment. The Result of dashboard design that can show and monitoring data of lecturers, employees, college student, research faculty, and completed research.